Management of mandibular basilar fracture as a complication of tumor surgery - Sergio Monteiro Lima Junior; Bruno Ramos Chrcanovic; Leonardo Gomes; Leandro Napier Souza; Ricardo Santiago Gomez; Belini Freire-Maia (Universidade Estadual de Campinas, 2015)
Fracture of the mandible basilar bone after a conservative resection of an ameloblastoma is an unusual postoperative complication and poorly cited in literature, since the radical resection is the most common treatment used for this condition. We present a case dealing with this complication, showing a technique for mandibular reconstruction that creates good results in five years of follow-up.